La conoscenza per il progetto Il case-based reasoning nell'architettura e nel design - Zambelli, Matteo (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
Case-based reasoning is a cognitive model developed to explain how people reason in problem solving. According to this model, a person resorts to knowledge and strategies used in the past to solve or understand a problem that is similar to the current one. Case-based reasoning applied to design is called case-based design. La conoscenza per il progetto explains the scientific reasons and why knowledge is crucial to be a good designer and proposes a method for analysing, breaking down and archiving cases of architecture and design (but not only), the typical knowledge of designers, in order to be able to consciously reuse it in a new project.